Subscales of the Fear Survey Schedule-III in Community Dwelling Older Adults – Relations to Clinical and Cognitive Measures. Issue 3 (3rd May 2020) - Mohlman, Jan; Lauderdale, Sean; Wuthrich, Viviana
ABSTRACT: Objectives: One major obstacle to the diagnosis and treatment of specific phobias in later life is the lack of assessment tools that are relevant to the fears of older adults. This study investigated the utility of five reliable subscales (Blood/Injury, Agoraphobia, Aggression, Animal/Insect, Social Fears) derived from the Fear Survey Schedule-III, a popular measure of phobic fear, in discriminating older from younger participants. Method: The sample was comprised of 81 younger and 61 older adults who completed self-report measures of anxiety and depression and neuropsychological tests. Results: Older adults scored significantly higher than their younger counterparts only on the Aggression subscale of the FSS-III; whereas younger adults scored significantly higher than the older group only on the Social Fears subscale. These subscales showed slightly different associations with other measures of anxiety, depression, and intelligence across age groups. Within the older sample, scores on the Aggression subscale were significantly higher than all other subscales except for Social Fears. Conclusions: It is recommended that clinicians and researchers use subscale scores derived from the FSS-III, rather than total scores, when treating and studying fears of later life. Clinical Implications: Use of FSS-III subscales in assessment could result in improved detection and treatment of phobias in later life, and thus raise quality of life among the elderly. Older adults' fears of victimization should be prioritized as a possible treatment target in clinical settings.